2008
DOI: 10.1210/en.2008-0439
|View full text |Cite
|
Sign up to set email alerts
|

Role of Akt/GSK-3β/β-Catenin Transduction Pathway in the Muscle Anti-Atrophy Action of Insulin-Like Growth Factor-I in Glucocorticoid-Treated Rats

Abstract: Decrease of muscle IGF-I plays a critical role in muscle atrophy caused by glucocorticoids (GCs) because IGF-I gene electrotransfer prevents muscle atrophy caused by GCs. The goal of the present study was to identify the intracellular mediators responsible for the IGF-I anti-atrophic action in GC-induced muscle atrophy. We first assessed the IGF-I transduction pathway alterations caused by GC administration and their reversibility by local IGF-I overexpression performed by electrotransfer. Muscle atrophy induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 54 publications
(62 reference statements)
3
58
0
2
Order By: Relevance
“…According to some researches for mammals, excessive glucocorticoids causing skeletal muscle atrophy in avian might be due to: (1) promoting proteolysis in muscle by stimulating the expression of proteins such as E3-ligases, atrogin-1, MuRF-1 (muscle ring finger 1), and the lysosomal enzyme cathepsin L in the ubiquitinproteolytic pathways (Auclair et al 1997;Hasselgren 1999;Marinovic et al 2002;Combaret et al 2005;Baehr et al 2010); (2) limiting the protein synthesis by inhibiting the transport of amino acids into the muscle and inhibiting the stimulatory action of insulin, IGF-I (insulin-like growth factor-I), and amino acids on the phosphorylation of eIF4E-binding protein 1 (4E-BP1) and the ribosomal protein S6 kinase 1 (S6K1) (Shah et al 2000a, b;Liu et al 2004;Schakman et al 2008b). In addition, the upregulation of myostatin and FOXO and the downregulation of IGF-I and myogenin might take part responsibility for the dexamethasone-induced skeletal muscle atrophy in chick according to some researches for mammals in vitro as well in vivo (Lang et al 2001;Ma et al 2001Ma et al , 2003Sandri et al 2004;Gilson et al 2007;Du et al 2007;Schakman et al 2008b;Zheng et al 2010). However, the ultrastructural results in our study showed that the diminishment in skeletal muscle size was not only attributed to the dwindlement of myofibrils but to the decreases of glycogen granules, lipids and other components in in-termyofibrillar and interfilamentary spaces.…”
Section: Discussionmentioning
confidence: 99%
“…According to some researches for mammals, excessive glucocorticoids causing skeletal muscle atrophy in avian might be due to: (1) promoting proteolysis in muscle by stimulating the expression of proteins such as E3-ligases, atrogin-1, MuRF-1 (muscle ring finger 1), and the lysosomal enzyme cathepsin L in the ubiquitinproteolytic pathways (Auclair et al 1997;Hasselgren 1999;Marinovic et al 2002;Combaret et al 2005;Baehr et al 2010); (2) limiting the protein synthesis by inhibiting the transport of amino acids into the muscle and inhibiting the stimulatory action of insulin, IGF-I (insulin-like growth factor-I), and amino acids on the phosphorylation of eIF4E-binding protein 1 (4E-BP1) and the ribosomal protein S6 kinase 1 (S6K1) (Shah et al 2000a, b;Liu et al 2004;Schakman et al 2008b). In addition, the upregulation of myostatin and FOXO and the downregulation of IGF-I and myogenin might take part responsibility for the dexamethasone-induced skeletal muscle atrophy in chick according to some researches for mammals in vitro as well in vivo (Lang et al 2001;Ma et al 2001Ma et al , 2003Sandri et al 2004;Gilson et al 2007;Du et al 2007;Schakman et al 2008b;Zheng et al 2010). However, the ultrastructural results in our study showed that the diminishment in skeletal muscle size was not only attributed to the dwindlement of myofibrils but to the decreases of glycogen granules, lipids and other components in in-termyofibrillar and interfilamentary spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of both total muscle and myonuclear b-catenin occurs during exercise, load-induced muscle hypertrophy, and myocardial recovery after heart failure in vivo (Sakamoto et al 2004, Armstrong & Esser 2005, Braz et al 2009, and the Wnt/b-catenin pathway promotes insulin/IGF1-mediated reserve cell activation and myotube hypertrophy in vitro (Rochat et al 2004). The anti-atrophy effects of IGF1 in glucocorticoid-treated rats are via the AKT/GSK3b/b-catenin pathway (Schakman et al 2008). Moreover, b-catenin expression is necessary for physiological growth of muscle in adult animals (Armstrong et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, b-catenin is essential for adult skeletal muscle growth and regeneration in vivo , Reya & Clevers 2005, Armstrong et al 2006, and myonuclear b-catenin is up-regulated during overload-induced muscle hypertrophy in adults (Armstrong & Esser 2005). Muscle regrowth following atrophy is associated with downregulation of glycogen synthase kinase-3b (GSK3b), a negative regulator of b-catenin (van der Velden et al 2007, Schakman et al 2008. Finally, b-catenin promotes self-renewal of satellite stem cells (Perez-Ruiz et al 2008) Together, these findings suggest that Wnt/ b-catenin signaling plays an active role in the maintenance of body composition in adults.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic treatment of cultured muscle cells with dexamethasone (Dex) was shown to increase expression of the p85 subunit of PI3K, and Ueki et al reported that overexpression of the p85 subunit in mouse fibroblast cells created an imbalance among p110, p85, and IRS-1, leading to suppression of PI3K activity (25,26). Moreover, Schakman et al reported that expression of constitutively activated Akt, a dominant negative GSK-3β, or a stable β-catenin can block the muscle atrophy induced by Dex (27). Waddell et al reported that expression of the E3 ubiquitin ligase, MuRF1, is stimulated by the glucocorticoid receptor (GR) (or FoxO1), leading to increased muscle proteolysis by the ubiquitin-proteasome system (UPS) (28).…”
Section: Introductionmentioning
confidence: 99%